Synthesis and Characterization of Four New Trialkylammonium Sulfatotrioxochromates, [R3NH]2CrO3SO4, (R = Me, Et, n-Pr, n-Bu) - HAJIGHAHRAMANI, MARYAM; ZAMANPOOR, RASHID; GHAMMAMY, SHAHRIARE; MEHRANI, KHEYROLLAH; BANIBAIRAMI, TAHMINEH; RAHIMI, RAHMATTOLLAH; ASILI, SINA (Asian Journal of Chemistry, 2010)
The new mild chromium(VI) oxidizing agents i.e., trialkylammonium sulfatotrioxochromates (TriRASC), were prepared and characterized. These reagents are suitable for oxidizing various primary and secondary alcohols to their corresponding carbonyl compounds and anthracene to anthraquinone. Orange solids (TriRASC), is easily synthesized by the reaction of chromium(VI) oxide:trialkylamine: in 1:2 molar ratios and sufficient sulfuric acid. These reagents are versatile reagents for the effective and selective oxidation of organic substrates, in particular for alcohols, under mild conditions.